The effect of work-life balance, environment, and workload on nurse performance at Ken Saras Hospital - Maret Hari Suminarsih; Pitaloka Dharma Ayu; Muhammad Arif Rakhman (Universitas Widya Mataram, 2026)
This study investigates the effect of work-life balance, work environment, and workload on nurse performance at Ken Saras Hospital. Using a quantitative correlational design, data were collected from 109 nurses selected through purposive sampling. Questionnaires were employed as the primary data collection method, and the data were analyzed using multiple linear regression. The findings reveal that work-life balance and work environment have a positive and significant effect on nurse performance, while workload has a negative and significant effect. Among the variables, the work environment emerges as the most dominant factor influencing performance. Simultaneously, all three variables significantly affect nurse performance, with a contribution of 62%, indicating that these factors collectively play a substantial role. The study highlights that nurse performance is influenced by the interaction of individual, organizational, and job demand factors. It suggests that hospitals should enhance work-life balance, create supportive work environments, and manage workload effectively to improve overall nurse performance.